1986
DOI: 10.1093/nar/14.6.2779
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and comparison of the internal promoter, pE, of the ilvGMEDA operons fromEscherichia coliK-12 andSalmonella typhimurium

Abstract: It was previously determined that the distal portion of the ilvGMEDA operon was expressed despite the insertion of transposons into ilvG and ilvE. This observation suggested the existence of internal promoters upstream of ilvE (pE) and ilvD (pD). The internal promoter pE, responsible for part of ilvEDA expression, has been analyzed both in vivo and in vitro. Our results indicate that: pE exists in both E. coli K-12 and S. typhimurium; pE is located in the distal end of the ilvM coding sequence; the pE sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 51 publications
0
12
1
Order By: Relevance
“…The cat gene from pKK232-8 had previously been placed under the ilvEp promoter and used for a different purpose (16). The strain carrying the ilvEp-cat fusion, CU1648, offered a convenient system to examine whether ilvEp is regulated specifically by the availability of valine, isoleucine, and leucine, the end products of the pathway, or is affected by the growth rate of the cells as proposed earlier (21,33). Strain CU1648 carries the ilvEp promoter on a 100-bp HaeII-AatII fragment upstream of the promoterless cat gene, with about 50 bp upstream of the -35 region.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The cat gene from pKK232-8 had previously been placed under the ilvEp promoter and used for a different purpose (16). The strain carrying the ilvEp-cat fusion, CU1648, offered a convenient system to examine whether ilvEp is regulated specifically by the availability of valine, isoleucine, and leucine, the end products of the pathway, or is affected by the growth rate of the cells as proposed earlier (21,33). Strain CU1648 carries the ilvEp promoter on a 100-bp HaeII-AatII fragment upstream of the promoterless cat gene, with about 50 bp upstream of the -35 region.…”
Section: Resultsmentioning
confidence: 99%
“…It has been repeatedly observed that when cells are grown in rich medium (L broth), the genes of the ilv operon are more strongly repressed than they are in cells growing in the presence of all three branched-chain amino acids (9,21,33). Furthermore, this effect is independent of the operon promoter ilvGp (11,21). This repression might reflect a more general type of regulation, i.e., a growth rate-dependent control.…”
Section: Xrz5mentioning
confidence: 99%
See 3 more Smart Citations